Membrane electrode assembly for fuel cell and fuel cell
The fuel cell membrane electrode assembly addresses the issue of electrolyte membrane deformation and resistance by using a fibrous carbon material and polymer resin gas diffusion layer with controlled fiber diameter and roughness, enhancing durability and efficiency.
Patent Information
- Application Number
- JP2021567184
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-26
- Filing Date
- 2020-12-08
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2040-12-08
AI Technical Summary
The uneven thickness and irregularities in the gas diffusion layer containing conductive carbon fibers cause deformation of the electrolyte membrane, leading to increased resistance and void formation between the catalyst layer and the gas diffusion layer, which affects the efficiency and durability of the fuel cell.
The fuel cell membrane electrode assembly is designed with a gas diffusion layer composed of a fibrous carbon material and polymer resin, where the average fiber diameter of the carbon material is 25% or less of the catalyst layer thickness, and the arithmetic mean roughness of the gas diffusion layer surfaces is greater than that of the catalyst layer surfaces, ensuring close contact and flexibility to minimize deformation and voids.
This design reduces deformation of the electrolyte membrane, improves gas diffusivity, suppresses interfacial peeling, and enhances the durability and efficiency of the fuel cell by minimizing resistance and void formation.
Smart Images

Figure 0007599117000001 
Figure 0007599117000002 
Figure 0007599117000003
Abstract
Description
[Technical field]
[0001] The present invention primarily relates to a membrane electrode assembly for a fuel cell and a fuel cell. [Background technology]
[0002] A fuel cell is a highly efficient and clean power generating device that generates electricity and produces water through an electrochemical reaction between a fuel and an oxidant (hereinafter, each of which is simply referred to as gas). A fuel cell includes, for example, an electrolyte membrane, two catalyst layers arranged to sandwich the electrolyte membrane, two gas diffusion layers arranged to sandwich the electrolyte membrane between the catalyst layers, and two separators arranged to sandwich the electrolyte membrane between the gas diffusion layers. The gas diffused in the surface direction by the gas diffusion layers is oxidized or reduced by the catalyst layers. Increasing the gas diffusivity in the catalyst layers improves the efficiency of this electrochemical reaction.
[0003] Patent Document 1 proposes that in a gas diffusion layer arranged in contact with a separator having a groove-shaped fluid flow path, the gas diffusion layer is characterized by having a diffusion layer substrate having a pore size to thickness ratio of 0.35 or more, and when the diffusion layer substrate has conductive carbon fibers, the content of the conductive carbon fibers is set to 30% or more. In Patent Document 1, the diffusion layer substrate is formed into a sheet shape using, for example, conductive carbon fibers and thermoplastic resin. Examples of conductive carbon fibers include carbon fibers, carbon paper, and carbon cloth. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2019-153416 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, when the gas diffusion layer contains conductive carbon fibers, depending on the thickness of the fibers and the thickness of the catalyst layer, the surface of the catalyst layer in contact with the electrolyte membrane may become uneven, which may damage the electrolyte membrane and form large gaps between the gas diffusion layer and the catalyst layer.
[0006] For example, when the gas diffusion layer has a diffusion layer substrate containing conductive carbon fibers as in Patent Document 1, large irregularities are formed by the conductive carbon fibers. As a result, the catalyst layer may also have irregularities that correspond to the irregularities of the gas diffusion layer, causing the electrolyte membrane to deform significantly. When the electrolyte membrane deforms, deterioration of the electrolyte membrane is accelerated starting from the deformed area. On the other hand, when the catalyst layer does not follow the irregularities of the gas diffusion layer, large gaps are formed between the gas diffusion layer and the catalyst layer, causing an increase in resistance and retention of generated water. [Means for solving the problem]
[0007] One aspect of the present invention relates to a membrane electrode assembly for a fuel cell (first membrane electrode assembly for a fuel cell) having a catalyst layer having a first main surface and a second main surface, a gas diffusion layer arranged on the first main surface side, and an electrolyte membrane arranged on the second main surface side, wherein the gas diffusion layer contains a conductive material and a polymer resin, the conductive material contains a fibrous carbon material, an average fiber diameter D of the fibrous carbon material is 25% or less of a thickness T of the catalyst layer, and in a cross section in the thickness direction of the catalyst layer, an arithmetic mean roughness Ra1 of the first main surface and an arithmetic mean roughness Ra2 of the second main surface satisfy the relationship Ra1>Ra2.
[0008] Another aspect of the present invention relates to a membrane electrode assembly for a fuel cell (second membrane electrode assembly for a fuel cell), comprising: an electrolyte membrane; a pair of catalyst layers arranged to sandwich the electrolyte membrane; and a pair of gas diffusion layers arranged to sandwich the electrolyte membrane via the pair of catalyst layers, each of the pair of catalyst layers having a first main surface and a second main surface, the gas diffusion layer being arranged on the first main surface side and the electrolyte membrane being arranged on the second main surface side, at least one of the pair of gas diffusion layers comprising a conductive material and a polymer resin, the conductive material comprising a fibrous carbon material, an average fiber diameter D of the fibrous carbon material being 25% or less of a thickness T of the catalyst layer, and in a cross section in the thickness direction of the catalyst layer, an arithmetic mean roughness Ra1 of the first main surface and an arithmetic mean roughness Ra2 of the second main surface satisfy the relationship Ra1>Ra2.
[0009] Yet another aspect of the present invention relates to a fuel cell comprising a second membrane electrode assembly for a fuel cell, and a pair of separators arranged to sandwich the membrane electrode assembly for a fuel cell, respectively via the pair of gas diffusion layers provided in the second membrane electrode assembly for a fuel cell. Effect of the Invention
[0010] The membrane electrode assembly for a fuel cell according to the present invention can reduce damage caused by deformation of the electrolyte membrane, and can also reduce voids that may form between the gas diffusion layer and the catalyst layer. The novel features of the present invention are set forth in the appended claims, but the present invention, both in terms of structure and content, together with other objects and features of the present invention, will be better understood from the following detailed description taken in conjunction with the drawings. [Brief description of the drawings]
[0011] [Figure 1] 1 is a cross-sectional view showing a schematic structure of a single cell of a fuel cell according to the present invention. [Diagram 2] 1 is a cross-sectional view that illustrates a schematic structure of a membrane electrode assembly according to the present invention. [Diagram 3]2 is an illustration of a cathode side region of a SEM image of a cross section of a membrane electrode assembly for a fuel cell according to Example 1. [Figure 4] FIG. 4 is an enlarged view of a portion of FIG. [Diagram 5] 1 is an illustration of a cathode side region of an SEM image of a cross section of a fuel cell membrane electrode assembly according to Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] A fuel cell membrane electrode assembly according to a first embodiment of the present invention includes a catalyst layer having a first main surface and a second main surface, a gas diffusion layer disposed on the first main surface side, and an electrolyte membrane disposed on the second main surface side. The gas diffusion layer includes a conductive material (hereinafter also referred to as a first conductive material) and a polymer resin (hereinafter also referred to as a first polymer resin), the first conductive material includes a first fibrous carbon material, and the average fiber diameter D of the first fibrous carbon material is 25% or less of the thickness T of the catalyst layer. Here, the combination of the catalyst layer and the gas diffusion layer may constitute an anode or a cathode.
[0013] A fuel cell membrane electrode assembly according to a second embodiment of the present invention includes an electrolyte membrane, a pair of catalyst layers arranged to sandwich the electrolyte membrane, and a pair of gas diffusion layers arranged to sandwich the electrolyte membrane via the pair of catalyst layers. Each of the pair of catalyst layers has a first main surface and a second main surface, with the gas diffusion layer arranged on the first main surface side and the electrolyte membrane arranged on the second main surface side.
[0014] In the second embodiment, at least one of the pair of catalyst layers corresponds to the combination of the catalyst layer and the gas diffusion layer according to the first embodiment. That is, at least one of the pair of gas diffusion layers contains a first conductive material and a first polymer resin, the first conductive material contains a first fibrous carbon material, and the average fiber diameter D of the first fibrous carbon material is 25% or less of the thickness T of the catalyst layer.
[0015] In the second embodiment, one of the pair of combinations of a catalyst layer and a gas diffusion layer constitutes one of the anode and the cathode, and the other of the pair of combinations of a catalyst layer and a gas diffusion layer constitutes the other of the anode and the cathode.
[0016] Furthermore, a fuel cell according to yet another embodiment of the present invention comprises a fuel cell membrane electrode assembly according to the second embodiment, and a pair of separators arranged to sandwich the fuel cell membrane electrode assembly via a pair of gas diffusion layers provided in the second fuel cell membrane electrode assembly.
[0017] In other words, at least one of the gas diffusion layers may contain a first conductive material and a first polymer resin, the first conductive material may contain a first fibrous carbon material, and the average fiber diameter D of the first fibrous carbon material may be 25% or less of the thickness T of the catalyst layer. Alternatively, both gas diffusion layers may contain independent first conductive materials and independent first polymer resins, each of the first conductive materials may contain the first fibrous carbon material, and the average fiber diameter D of each of the first fibrous carbon materials may be 25% or less of the thickness T of the corresponding catalyst layer.
[0018] When the gas diffusion layer includes a first conductive material and a first polymer resin, and the first conductive material includes a first fibrous carbon material, the mechanical strength of the gas diffusion layer is improved, and the design of the gas diffusion properties of the gas diffusion layer is facilitated, enabling smoother gas diffusion and suppressing pressure loss. In addition, by appropriately controlling the gas diffusion properties, the humidity of the electrolyte membrane is easily maintained at an appropriate level.
[0019] When the average fiber diameter D of the first fibrous carbon material is 25% or less of the thickness T of the catalyst layer (i.e., when the first fibrous carbon is sufficiently thin with respect to the thickness T of the catalyst layer), the unevenness on the first main surface side of the gas diffusion layer becomes sufficiently small relative to the thickness of the catalyst layer, and the effect of the unevenness on the electrolyte membrane is reduced. In addition, by using a gas diffusion layer including a first fibrous carbon that is sufficiently thin with respect to the thickness T of the catalyst layer and a first polymer resin, the elasticity or flexibility of the first polymer resin is fully expressed, and the gas diffusion layer can flexibly plastically deform in accordance with the shape of the unevenness of the catalyst layer. This further reduces the effect of the gas diffusion layer on the electrolyte membrane. These actions greatly reduce the deformation of the electrolyte membrane. As a result, localized current concentration in the electrolyte membrane is suppressed, and the durability of the electrolyte membrane (and further the catalyst layer) is further improved. Furthermore, the unevenness on the first main surface side of the gas diffusion layer is sufficiently small relative to the thickness of the catalyst layer, and the gas diffusion layer can flexibly undergo plastic deformation to match the unevenness of the catalyst layer, which facilitates adhesion between the gas diffusion layer and the catalyst layer and reduces the amount of voids that may be formed between the gas diffusion layer and the catalyst layer. As a result, interfacial peeling between the catalyst layer and the gas diffusion layer is easily suppressed, gas diffusibility to the catalyst layer is further improved, and resistance is reduced.
[0020] Here, in the cross section in the thickness direction of the catalyst layer, the arithmetic mean roughness Ra1 of the first main surface and the arithmetic mean roughness Ra2 of the second main surface satisfy the relationship Ra1>Ra2. Even if the unevenness on the first main surface side of the gas diffusion layer is sufficiently small relative to the thickness of the catalyst layer and the gas diffusion layer can flexibly plastically deform in accordance with the shape of the unevenness of the catalyst layer, if the relationship Ra1>Ra2 is not satisfied (if Ra1≦Ra2), it may be difficult to sufficiently suppress the deformation of the electrolyte membrane and sufficiently reduce damage caused by the deformation of the electrolyte membrane. In addition, if Ra1≦Ra2, the movement of gas from the first main surface to the second main surface tends to stagnate, or the movement of moisture generated in the catalyst layer to the gas diffusion layer tends to stagnate. To satisfy Ra1>Ra2, for example, as described later, it is effective to once form the catalyst layer on a transfer base sheet having a flat surface.
[0021] More preferably, the ratio of the arithmetic mean roughness Ra1 of the first main surface to the arithmetic mean roughness Ra2 of the second main surface: Ra1 / Ra2 may satisfy 2≦Ra1 / Ra2. When such a relationship is satisfied, damage caused by deformation of the electrolyte membrane is highly reduced, and the resistance between the gas diffusion layer and the catalyst layer is easily suppressed. However, Ra1 and Ra2 are interrelated. It is preferable that the unevenness at the interface between the gas diffusion layer and the catalyst layer is considerably small from the viewpoint of reducing the deformation of the electrolyte membrane by reducing Ra2. In addition, the smaller the unevenness at the interface between the gas diffusion layer and the catalyst layer, the more advantageous it is in reducing the gap that may be formed between the gas diffusion layer and the catalyst layer. In consideration of these, it is desirable that Ra1 is considerably small, and it is desirable to satisfy, for example, Ra1 / Ra2<10 or Ra1 / Ra2<5.
[0022] It is desirable that the thickness T of the catalyst layer is formed as thin as possible from the viewpoint of reducing the amount of expensive catalyst used and reducing resistance. On the other hand, from the viewpoint of the strength of the catalyst layer, it is preferable that the thickness is not excessively thin. The thickness T of the catalyst layer may be, for example, 1 μm or more, and may be 5 μm or more. The thickness T of the catalyst layer may be, for example, 20 μm or less, 10 μm or less, or 5 μm or less. The thickness T of the catalyst layer may be 1 μm or more and 20 μm or less, 1 μm or more and 10 μm or less, or 5 μm or more and 10 μm or less.
[0023] The thickness T of the catalytic layer is an average thickness, and is obtained by averaging the distances when a straight line is drawn along the thickness direction of the catalytic layer from the first main surface to the second main surface for any ten points on the cross section of the catalytic layer.
[0024] The arithmetic mean roughness Ra1 of the first principal surface may be 30% or less of the thickness T of the catalyst layer. In this case, since the irregularities of the catalyst layer on the first principal surface side are sufficiently small compared to the thickness T of the catalyst layer, it is easy to achieve high adhesion between the gas diffusion layer and the catalyst layer while ensuring sufficient strength of the catalyst layer.
[0025] The arithmetic mean roughness Ra1 of the first main surface may be 10% or more of the thickness T of the catalyst layer. In this case, the gas diffusion layer is caused to bite into the irregularities of the catalyst layer, thereby increasing the bonding strength between the gas diffusion layer and the catalyst layer, making it easier to suppress peeling between the gas diffusion layer and the catalyst layer.
[0026] The arithmetic mean roughness Ra2 of the second main surface may be 5% or less of the catalyst layer thickness T. In this case, deformation of the electrolyte membrane becomes extremely small, and the effect of reducing damage caused by deformation of the electrolyte membrane becomes significant.
[0027] As described above, it is desirable that the arithmetic mean roughness Ra1 of the first principal surface is considerably small. From the viewpoint of achieving high adhesion between the gas diffusion layer and the catalyst layer while ensuring sufficient strength of the catalyst layer, the arithmetic mean roughness Ra1 of the first principal surface may be, for example, 2 μm or less, or 1.5 μm or less.
[0028] Furthermore, from the viewpoint of increasing the bonding strength between the catalyst layer and the gas diffusion layer by making the gas diffusion layer bite into the irregularities of the catalyst layer, Ra1 may be 0.6 μm or more.
[0029] Moreover, from the viewpoint of significantly suppressing deformation of the electrolyte membrane, it is desirable for the arithmetic mean roughness Ra2 of the second principal surface to be even smaller, and Ra2 may be, for example, 0.3 μm or less, or 0.2 μm or less.
[0030] The arithmetic mean roughness Ra1 of the first main surface and the arithmetic mean roughness Ra2 of the second main surface can be measured by the following method. First, a cross section along the lamination direction (thickness direction) of the laminate of the catalyst layer and the gas diffusion layer is photographed to obtain an SEM image. The magnification of the SEM image is 1000 times to 5000 times. For example, when the size in one direction of the display screen is 10 cm and the scanning width of the SEM scanning probe in the one direction is 100 μm, the magnification is 1000 times. In the obtained SEM image, cross-sectional curves of the first and second main surfaces of the catalyst layer according to JIS B 0601 (2001) are obtained and converted into roughness curves, and the arithmetic mean roughness Ra is obtained from the obtained roughness curve. The scanning width of the SEM scanning probe is 50 μm or more.
[0031] The average fiber diameter D may be 25% or less of the thickness T of the catalyst layer, but in order to easily suppress Ra1 to be small, it is desirable that the average fiber diameter D is sufficiently smaller than the arithmetic mean roughness Ra1 of the first main surface of the catalyst layer, and more desirably, the average fiber diameter D is sufficiently smaller than the arithmetic mean roughness Ra2 of the second main surface of the catalyst layer. Specifically, the average fiber diameter D may be, for example, 250 nm or less, or 170 nm or less. In this case, it is also preferable in terms of sufficiently securing fine gas paths. The lower limit of the average fiber diameter D is not particularly limited, but may be, for example, 5 nm or more from the viewpoint of reducing resistance by making the first fibrous carbon material an electron path. That is, the average fiber diameter D may be 5 nm or more and 250 nm or less, or 5 nm or more and 170 nm or less.
[0032] The average fiber diameter D is determined by randomly taking 10 pieces of the first fibrous carbon material from the gas diffusion layer and averaging their diameters. The diameter is the length in the direction perpendicular to the longitudinal direction of the first fibrous carbon material.
[0033] The average length L of the first fibrous carbon material is not particularly limited. The average length L of the first fibrous carbon material may be, for example, 0.2 μm or more, and may be 0.5 μm or more. The average length L1 of the first fibrous carbon material may be, for example, 20 μm or less, and may be 10 μm or less. When the average length L is in this range, the mechanical strength of the gas diffusion layer is further improved, and the design of the gas diffusion property of the gas diffusion layer is easier, which is advantageous for suppressing pressure loss. The average length L is obtained by arbitrarily taking 10 pieces of the first fibrous carbon material from the gas diffusion layer and averaging the actual lengths of these pieces.
[0034] As described above, it is desirable that the gap formed between the gas diffusion layer and the catalyst layer is as small as possible. However, gaps inevitably exist in the interface region between the catalyst layer and the gas diffusion layer. Such gaps become the gas path from the gas diffusion layer to the catalyst layer. Specifically, the dimension Wk of the gap in the direction along the interface is desirably equal to or less than the thickness T of the catalyst layer, and may be equal to or less than 0.8×T, or may be equal to or less than 0.4×T. If Wk is equal to or less than T, even if such gaps exist, the path through which electrons go around is not large, and an increase in resistance is suppressed. In addition, cracks are unlikely to occur in the catalyst layer, and the shape of the catalyst layer is likely to be maintained. In this case, the dimension Ws of the gap in the thickness direction of the catalyst layer is desirably equal to or less than Wk, and may be equal to or less than 0.8×Wk. When Ws is equal to or less than Wk, the generated water (or back-diffused water) is likely to be discharged without remaining at the interface between the gas diffusion layer and the catalyst layer, so that the gas diffusion property is unlikely to decrease and the gas diffusion layer is unlikely to peel off. In addition, even if a part of the catalyst layer is damaged and falls into the gap, the function of the catalyst layer is likely to be maintained.
[0035] The configuration of the gas diffusion layer will be specifically described below. (Gas diffusion layer) The gas diffusion layer may contain a first conductive material and a first polymer resin, but is preferably a "porous member mainly composed of a first conductive material and a first polymer resin." Here, "a porous member mainly composed of a first conductive material and a first polymer resin" means a porous member having a structure supported by the first conductive material and the first polymer resin (so-called self-supporting structure) without having a woven or nonwoven fabric such as carbon paper or carbon cloth as a substrate. Note that the gas diffusion layer may have such a region without a substrate with a sufficient thickness (e.g., 30 μm or more), and the surface of the gas diffusion layer on the side not in contact with the catalyst layer may be composed of the substrate as described above.
[0036] When manufacturing a porous member from a first conductive material and a first polymer resin, for example, a surfactant and a dispersion medium are used as described below. In this case, during the manufacturing process, the surfactant and the dispersion medium are removed by baking, but they may not be sufficiently removed and may remain in the porous member. Therefore, "a porous member mainly composed of a first conductive material and a first polymer resin" means that the surfactant and the dispersion medium remaining in this way may be contained in the porous member as long as the structure is supported by the first conductive material and the first polymer resin. It also means that materials other than the first conductive material, the first polymer resin, the surfactant, and the dispersion medium may be contained in the porous member.
[0037] The first conductive material preferably contains the first fibrous carbon material as a main component. For example, the mass ratio of the first fibrous carbon material in the gas diffusion layer may be 10 mass% or more and 90 mass% or less, or 20 mass% or more and 75 mass% or less. In terms of easily ensuring sufficient gas diffusivity, it is desirable that the mass ratio of the first fibrous carbon material is high. On the other hand, by appropriately controlling the mass ratio of the first fibrous carbon material, it becomes easier to reduce resistance.
[0038] Considering the miniaturization of the fuel cell, it is desirable that the thickness of the gas diffusion layer is thin. On the other hand, from the viewpoint of strength, it is preferable that the gas diffusion layer is not excessively thin. The thickness of the gas diffusion layer is, for example, 30 μm or more and 1000 μm or less, preferably 50 μm or more and 500 μm or less, and may be 80 μm or more and 300 μm or less.
[0039] The thickness of the gas diffusion layer is an average thickness, and is obtained by averaging the distances when a straight line is drawn along the thickness direction of the gas diffusion layer from one main surface to the other main surface at any 10 points on the cross section of the gas diffusion layer.
[0040] <First fibrous carbon material> The first fibrous carbon material has an aspect ratio of 2 or more and is conductive. The aspect ratio of the first fibrous carbon material may be 3 or more, or 5 or more. The aspect ratio of the first fibrous carbon material may be 1000 or less, 500 or less, or 100 or less. The aspect ratio of the first fibrous carbon material is, for example, 3 or more and 1000 or less. The aspect ratio of the first fibrous carbon material is the ratio (L / D) of the average length L to the average fiber diameter D of the first fibrous carbon material.
[0041] Examples of the first fibrous carbon material include vapor grown carbon fiber (VGCF (registered trademark)), single-walled or multi-walled carbon nanotubes (CNT), and carbon nanofibers. The first fibrous carbon material may have a hollow space (hollow portion) inside. Both ends in the length direction of the first fibrous carbon material may be open.
[0042] The first fibrous carbon material may be a mixture of two or more materials having different average fiber diameters D and / or average lengths L. For example, the first fibrous carbon material may contain single-walled carbon nanotubes and multi-walled carbon nanotubes.
[0043] <First polymer resin> The first polymer resin functions as a binder that binds the first conductive material together. From the viewpoint of suppressing water retention in the gas diffusion layer, it is preferable that 50% by mass or more, and further 90% by mass or more of the first polymer resin is a water-repellent resin. The polymer resin may further contain a proton conductive resin (polymer electrolyte). The mass ratio of the first polymer resin in the gas diffusion layer may be 5% by mass or more and 50% by mass or less, or 10% by mass or more and 40% by mass or less.
[0044] Examples of water-repellent resins include fluororesins. Examples of fluororesins include PTFE (polytetrafluoroethylene), FEP (tetrafluoroethylene-hexafluoropropylene copolymer), PVdF (polyvinylidene fluoride), ETFE (tetrafluoroethylene-ethylene copolymer), PCTFE (polychlorotrifluoroethylene), and PFA (tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer). Among these, from the viewpoints of heat resistance, water repellency, and chemical resistance, the fluororesin is preferably PTFE.
[0045] The proton conductive resin is not particularly limited. Examples of the proton conductive resin include perfluorocarbon sulfonic acid polymers and hydrocarbon polymers. Among them, perfluorocarbon sulfonic acid polymers and the like are preferred because of their excellent heat resistance and chemical stability. Examples of the perfluorocarbon sulfonic acid polymers include Nafion (registered trademark).
[0046] <Other> The gas diffusion layer may contain, as a conductive material, a particulate carbon material, a plate-like carbon material, or the like.
[0047] The particulate carbon material has an aspect ratio of less than 2 and is conductive. The particulate carbon material is not particularly limited, but examples thereof include carbon black, spherical graphite, and activated carbon. Among them, carbon black is preferred because of its high conductivity and large pore volume. Examples of carbon black include acetylene black, ketjen black, thermal black, furnace black, and channel black. The particle size (or the length of the structure composed of a plurality of connected primary particles) may be that which is conventionally used in the gas diffusion layer of a fuel cell.
[0048] The average particle size of the primary particles of the particulate carbon material is preferably 250 nm or less, and may be 170 nm or less. The average particle size of the primary particles may be determined as the average of the maximum diameters of 100 primary particles of the particulate carbon material observed under a microscope.
[0049] The mass proportion of the particulate carbon material in the gas diffusion layer is not particularly limited, but from the viewpoint of gas diffusivity, the mass proportion of the particulate carbon material in the gas diffusion layer may be 30 mass% or less, or may be 20 mass% or less.
[0050] Specific examples of the plate-like carbon material include flake graphite, pulverized graphitized polyimide film, graphene, etc. Among them, pulverized graphitized polyimide film and graphene are easily oriented in the surface direction, which is advantageous for forming a thin gas diffusion layer and is suitable for increasing gas diffusivity in the surface direction.
[0051] The thickness of the carbon material plate is preferably 250 nm or less, and may be 170 nm or less. The thickness of the carbon material plate can be determined as the average value of the maximum thicknesses of 100 particles of the carbon material plate observed under a microscope.
[0052] The mass proportion of the plate-shaped carbon material in the gas diffusion layer is not particularly limited, but from the viewpoint of gas diffusivity, the mass proportion of the plate-shaped carbon material in the gas diffusion layer may be 30 mass% or less, or may be 20 mass% or less.
[0053] <Method of manufacturing gas diffusion layer> The gas diffusion layer is obtained, for example, by forming a mixture containing a conductive material such as a first fibrous carbon material, a first polymer resin, and a dispersion medium into a sheet and baking it. For example, water, alcohol (ethanol, propanol, etc.) are used as the dispersion medium. At this time, a surfactant may be added to the mixture. For example, polyoxyethylene alkyl ether, alkylamine oxide, etc. may be used as the surfactant. The surfactant may be appropriately selected depending on the type of the first conductive material and the dispersion medium. More specifically, the first conductive material, the first polymer resin, the surfactant, and the dispersion medium are kneaded, and the resulting mixture is formed into a sheet.
[0054] When forming the mixture into a sheet, for example, the mixture may be rolled using a roll press or a flat press, or may be fed into an extruder and continuously formed into a sheet from a die head. The sheet may be further rolled. A roll press may be used for rolling. The conditions for the roll press are not particularly limited, but a gas diffusion layer with high strength can be easily obtained by rolling at a linear pressure of 0.001 ton / cm to 4 ton / cm.
[0055] The molded sheet may be fired. The firing removes the surfactant and the dispersion medium from the mixture. The mixture may be heated at the same time as rolling. The firing temperature and firing time may be such that the surfactant and the dispersion medium evaporate or decompose. The firing temperature is preferably equal to or lower than the melting point of the first polymer resin (e.g., 330°C to 350°C). The evaporation or decomposition temperature of the surfactant is generally 260°C or higher. Therefore, the firing temperature is preferably equal to or higher than 260°C.
[0056] The fired sheet may be further rolled. This allows the thickness of the sheet to be adjusted. A die having ribs arranged along a predetermined gas flow path pattern may be used for the rolling after firing. This allows gas flow paths to be formed in the gas diffusion layer. The gas flow paths may be formed by cutting the main surface of the fired sheet.
[0057] The structure of the catalyst layer will be specifically described below. (catalyst layer) The catalyst layer includes a conductive material (hereinafter also referred to as a second conductive material), catalyst particles, and a polymer resin (hereinafter also referred to as a second polymer resin). Examples of the second conductive material include a material having the same or similar physical properties as the first conductive material. In particular, the second conductive material preferably includes a second fibrous carbon material having the same or similar physical properties as the first fibrous carbon material (i.e., a fibrous carbon material having an average fiber diameter D2 of 25% or less of the thickness T of the catalyst layer). In this case, it becomes easy to control the arithmetic mean roughness Ra1 of the first main surface of the catalyst layer to 0.6 μm or more.
[0058] The content of the second conductive material in the catalyst layer may be, for example, 1 mass % or more and 85 mass % or less, and more preferably 5 mass % or more and 75 mass % or less, relative to the total of the second conductive material, the catalyst particles, and the second polymeric resin.
[0059] <Catalyst particles> The catalyst particles are not particularly limited, and may be at least one or more alloys selected from the group consisting of Sc, Y, Ti, Zr, V, Nb, Fe, Co, Ni, Ru, Rh, Pd, Pt, Os, Ir, lanthanoid series elements, and actinoid series elements. For example, the catalyst particles used in the anode include Pt-Ru alloys, etc. The catalyst metals used in the cathode include Pt and Pt-Co alloys, etc.
[0060] <Second polymer resin> The second polymer resin functions as a binder that binds the second conductive materials together. From the viewpoint of improving reactivity, the second polymer resin preferably contains a proton conductive resin. The proton conductive resin may be, for example, the same material as that used in the gas diffusion layer. The proton conductive resin is preferably contained in an amount of 50 parts by mass or more and 200 parts by mass or less with respect to 100 parts by mass of the second conductive material contained in the catalyst layer.
[0061] (Method of manufacturing catalyst layer) The catalyst layer can be formed, for example, by applying a catalyst ink containing a second conductive material, catalyst particles, a second polymer resin, and a dispersion medium to the surface of a predetermined substrate and drying the same. For example, an electrolyte membrane or a transfer substrate sheet may be used as the substrate. When an electrolyte membrane is used as the substrate, the catalyst layer may be formed by directly applying the catalyst ink to the electrolyte membrane. Alternatively, the catalyst ink may be applied to a transfer substrate sheet having a flat surface, and the catalyst layer may be transferred to the gas diffusion layer after drying. This improves the flatness of the second main surface of the catalyst layer that contacts the electrolyte membrane. As the application method, a screen printing method and a coating method using various coaters such as a blade coater, a knife coater, a gravure coater, and a die coater are preferable.
[0062] As the base sheet, it is preferable to use a sheet having a smooth surface, such as polyethylene terephthalate (PET) or polypropylene.
[0063] (Method of manufacturing membrane electrode assembly) As described above, when the electrolyte membrane is used as the base material, the catalyst ink is directly applied to the electrolyte membrane, and a catalyst layer having a first main surface and a second main surface is formed so that the second main surface contacts the electrolyte membrane. In this case, a membrane electrode assembly can be obtained by subsequently attaching a gas diffusion layer to the first main surface of the catalyst layer of the assembly of the electrolyte membrane and the catalyst layer. In addition, when a transfer base sheet is used, a catalyst layer having a first main surface and a second main surface is formed on a base sheet having a flat surface so that the second main surface contacts the flat surface. Next, a gas diffusion layer is laminated on the catalyst layer so as to contact the first main surface of the catalyst layer. Then, the base sheet is peeled off from the second main surface of the catalyst layer, and an electrolyte membrane is attached to the second main surface of the catalyst layer to obtain a membrane electrode assembly. In this case, by setting the average fiber diameter D of the first fibrous carbon material to 25% or less of the thickness T of the catalyst layer, the unevenness in the first main surface of the gas diffusion layer becomes sufficiently small relative to the thickness of the catalyst layer, making it possible to reduce deformation of the electrolyte membrane caused by the unevenness in the gas diffusion layer and to reduce voids that may be formed between the gas diffusion layer and the catalyst layer. Furthermore, in a cross section in the thickness direction of the catalyst layer, the arithmetic mean roughness Ra1 of the first main surface and the arithmetic mean roughness Ra2 of the second main surface can easily satisfy the relationship Ra1>Ra2.
[0064] The configuration of the fuel cell will be specifically described below. [Fuel cell] The fuel cell includes a first separator and a second separator arranged to sandwich the membrane electrode assembly with a first gas diffusion layer and a second gas diffusion layer interposed therebetween. Specifically, the fuel cell includes a membrane electrode assembly (hereinafter, MEA) having an electrolyte membrane, a cathode in contact with one main surface of the electrolyte membrane, and an anode in contact with the other main surface of the electrolyte membrane, a conductive cathode separator (first separator) in contact with the cathode, and a conductive anode separator (second separator) in contact with the anode. The MEA and the pair of separators form one cell. Usually, a stack is formed in which the cells are connected in series by stacking a plurality of cells so that the cathode separator and the anode separator are adjacent to each other.
[0065] Referring to FIG. 1, the cell 1 has a membrane electrode assembly (MEA) 5 including an anode 2, a cathode 3, and an electrolyte membrane 4 interposed between the anode 2 and the cathode 3. The MEA 5 is sandwiched between an anode separator 10 and a cathode separator 11. The anode 2 includes an anode catalyst layer (first catalyst layer) 6 in contact with the electrolyte membrane 4, and an anode gas diffusion layer (first gas diffusion layer) 7 in contact with the anode separator 10. The cathode 3 includes a cathode catalyst layer (second catalyst layer) 8 in contact with the electrolyte membrane 4, and a cathode gas diffusion layer (second gas diffusion layer) 9 in contact with the cathode separator 11. A gasket 14 is disposed on one side of the MEA 5 to seal the anode 2, and a gasket 15 is disposed on the other side to seal the cathode 3.
[0066] The anode separator 10 has a fuel flow path 12 that supplies fuel to the anode 2. The cathode separator 11 has an oxidant flow path 13 that supplies an oxidant to the cathode 3. A stack is formed by electrically stacking a plurality of cells as shown in FIG. 1 in series. In the stack, one surface of a separator may be used as an anode separator and the other surface may be used as a cathode separator. Alternatively, one surface of a separator may be used as an anode separator or a cathode separator, and the other surface may be used as a coolant flow path. Current collectors 16, 17 may be disposed on the outside of the cell or stack, respectively, and end plates 18, 19 may be disposed and fastened to each other to fix the fuel cell.
[0067] In the illustrated example, the fuel flow path 12 is formed on the main surface of the anode separator 10, and the oxidant flow path 13 is formed on the main surface of the cathode separator 11, but the fuel flow path may be formed on the main surface of the anode gas diffusion layer, and the oxidant flow path may be formed on the main surface of the cathode gas diffusion layer.
[0068] The present invention will be described in detail below with reference to examples, although the present invention is not limited to the following examples.
[0069] [Example 1] A membrane electrode assembly (MEA) was prepared as shown in Fig. 2. The MEA 5 includes an electrolyte membrane 4, an anode catalyst layer 6 and a cathode catalyst layer 8 arranged to sandwich the electrolyte membrane 4, an anode gas diffusion layer 7 arranged on the outer side of the anode catalyst layer 6, and a cathode gas diffusion layer 9 arranged on the outer side of the cathode catalyst layer 8.
[0070] (1) Preparation of the cathode gas diffusion layer 50 parts by mass of the first fibrous carbon material, 20 parts by mass of the particulate carbon material, and an appropriate amount of ethanol were mixed in a mixer, and then 30 parts by mass of PTFE were further added and mixed to obtain a mixture. CNT (average fiber diameter 0.15 μm, average length 6 μm) was used as the first fibrous carbon material. Acetylene black (average particle size 40 nm) was used as the particulate carbon material. The obtained mixture was formed into a sheet using an extrusion molding machine. Then, rolling and firing were performed to obtain a fired sheet from which the ethanol had been removed. The fired sheet was further rolled to adjust the thickness to 200 μm. The obtained sheet was cut into a desired shape to obtain a cathode gas diffusion layer.
[0071] Separately, a sheet of water-repellent carbon paper (thickness: 200 μm, average fiber diameter: 10 μm) was prepared as a gas diffusion layer for the anode.
[0072] (2) Preparation of cathode catalyst ink The second conductive material carrying catalyst particles (Pt-Co alloy) was added to an appropriate amount of water, and then stirred to disperse. The second conductive material was made of 40 parts by mass of CNT (average fiber diameter 0.15 μm, average length 6 μm) as the second fibrous carbon material, and 100 parts by mass of carbon black (average particle diameter 40 nm) as the particulate carbon material. An appropriate amount of ethanol was added to the obtained dispersion while stirring, and then 80 parts by mass of proton conductive resin (Nafion (registered trademark)) was added to 100 parts by mass of the second particulate carbon material carrying 30 parts by mass of catalyst particles to prepare a cathode catalyst ink.
[0073] (3) Preparation of anode catalyst ink The second conductive material carrying catalyst particles (Pt-Ru alloy) was added to an appropriate amount of water, and then stirred to disperse. Carbon black (average particle size 40 nm), a particulate carbon material, was used as the second conductive material. An appropriate amount of ethanol was added to the resulting dispersion while stirring, and then 80 parts by mass of proton conductive resin (Nafion (registered trademark)) was added to 100 parts by mass of the particulate carbon material carrying 30 parts by mass of catalyst particles to prepare an anode catalyst ink.
[0074] (4) Lamination of each layer The cathode catalyst ink was applied to the surface of a PET substrate sheet having a flat surface and dried to form a cathode catalyst layer (thickness 6 μm). The cathode catalyst layer was then transferred to one side of the cathode gas diffusion layer to form a cathode. The average fiber diameter D (0.15 μm) of the first fibrous carbon material of the cathode gas diffusion layer was 2.5% of the thickness T (6 μm) of the cathode catalyst layer.
[0075] The anode catalyst ink was applied to the surface of a PET substrate sheet having a flat surface and dried to form an anode catalyst layer (thickness 3 μm).The anode catalyst layer was then transferred to one side of the anode gas diffusion layer to form an anode.
[0076] Next, the electrolyte membrane was sandwiched between the anode and the cathode so that the anode catalyst layer and the cathode catalyst layer were in contact with the electrolyte membrane, and rolled to obtain a membrane electrode assembly (MEA) A1. As the electrolyte membrane, a Nafion membrane (registered trademark) having a thickness of 15 μm and a size slightly larger than the cathode was used.
[0077] [Rating 1] A cross section of the membrane electrode assembly (MEA) A1 was photographed with a scanning electron microscope (SEM). Figure 3 shows an illustration of the cathode side region of the SEM image. Figure 4 is an enlarged view of a portion of Figure 3. From each figure, it can be seen that the irregularities on the first main surface of the cathode gas diffusion layer are sufficiently small compared to the thickness of the catalyst layer.
[0078] A gap is inevitably formed between the cathode gas diffusion layer and the catalyst layer. The dimension Wk of the largest gap s observed by SEM in the direction along the interface between the cathode catalyst layer and the cathode gas diffusion layer was 1.5 μm or less, which was sufficiently smaller than the thickness T of the cathode catalyst layer. In addition, the dimension Ws of the gap in the thickness direction of the cathode catalyst layer was 0.6 μm, which was sufficiently smaller than Wk.
[0079] FIG. 4 was processed to determine the arithmetic mean roughness Ra1 of the first main surface and the arithmetic mean roughness Ra2 of the second main surface of the cathode catalyst layer. The results were Ra1=1.5 μm and Ra2=0.2 μm, respectively, which satisfied the relationship Ra1>Ra2.
[0080] [Comparative Example 1] (1) Preparation of gas diffusion layer Two sheets of water-repellent carbon paper (thickness: 200 μm, average fiber diameter: 10 μm) were prepared as the anode gas diffusion layer and the cathode gas diffusion layer.
[0081] (2) Preparation of cathode catalyst ink A cathode catalyst ink was prepared in the same manner as in Example 1.
[0082] (3) Preparation of anode catalyst ink An anode catalyst ink was prepared in the same manner as in Example 1.
[0083] (4) Lamination of each layer The cathode catalyst ink was applied to the surface of a PET substrate sheet having a flat surface, and then dried to form a cathode catalyst layer (thickness: 6 μm).
[0084] The anode catalyst ink was applied to the surface of a PET substrate sheet having a flat surface, and then dried to form an anode catalyst layer (thickness: 3 μm).
[0085] The same electrolyte membrane as in Example 1 was prepared, and a cathode catalyst layer and an anode catalyst layer were transferred onto each surface of the electrolyte.
[0086] Next, the cathode gas diffusion layer and the anode gas diffusion layer were sandwiched between the catalyst layer and the electrolyte membrane so that the cathode catalyst layer and the cathode gas diffusion layer were in contact with each other, and the anode catalyst layer and the anode gas diffusion layer were in contact with each other, to produce a membrane electrode assembly (MEA) B1. The average fiber diameter of the carbon paper in each gas diffusion layer was 10 μm, which was 167% of the thickness of the cathode catalyst layer, 6 μm.
[0087] [Rating 2] The cross section of the membrane electrode assembly (MEA) B1 was photographed with a scanning electron microscope (SEM). Figure 5 shows an illustration of the cathode side region of the SEM image. From Figure 5, it can be seen that the unevenness on the first main surface of the cathode gas diffusion layer is considerably large compared to the thickness of the catalyst layer. In Figure 5, a large cross section of the carbon paper F is observed, and it can be seen that it has a significant impact on the unevenness of the first main surface of the catalyst layer.
[0088] The dimension Wk of the maximum void S observed by SEM in the direction along the interface between the cathode catalyst layer and the cathode gas diffusion layer exceeded 10 μm and was considerably larger than the thickness T of the cathode catalyst layer.
[0089] FIG. 5 was subjected to image processing to determine the arithmetic mean roughness Ra1 of the first main surface and the arithmetic mean roughness Ra2 of the second main surface of the cathode catalyst layer, which were Ra1=4.5 μm and Ra2=4.6 μm, respectively. [Industrial Applicability]
[0090] The fuel cell according to the present invention can be suitably used particularly as a power source for vehicles, a power source for stationary home cogeneration systems, etc. The present invention is suitable for application to polymer electrolyte fuel cells, but is not limited thereto, and can be applied to fuel cells in general. Although the present invention has been described with respect to the presently preferred embodiments, such disclosure should not be interpreted as limiting. Various variations and modifications will no doubt become apparent to those skilled in the art to which the present invention pertains upon reading the above disclosure. Accordingly, the appended claims should be interpreted to cover all variations and modifications without departing from the true spirit and scope of the present invention. [Explanation of symbols]
[0091] 1 cell 2 Anode 3. Cathode 4 Electrolyte membrane 5 Membrane electrode assembly (MEA) 6 Anode catalyst layer 10 Anode separator 7 Anode gas diffusion layer 8. Cathode catalyst layer 11 Cathode separator 9 Cathode gas diffusion layer 14, 15 Gasket 12 Fuel flow passage 13 Oxidant flow path 16,17 Current collector plate 18,19 End plate
Claims
1. a catalyst layer having a first major surface and a second major surface; A gas diffusion layer disposed on the first main surface side; an electrolyte membrane disposed on the second main surface side, The gas diffusion layer includes a conductive material and a polymer resin, the conductive material includes a fibrous carbon material; an average fiber diameter D of the fibrous carbon material is 25% or less of a thickness T of the catalyst layer, In a cross section in the thickness direction of the catalyst layer, the arithmetic average roughness Ra1 of the first main surface and the arithmetic average roughness Ra2 of the second main surface are Ra1>Ra2 A membrane electrode assembly for a fuel cell that satisfies the above relationship.
2. 2. The membrane electrode assembly for a fuel cell according to claim 1, wherein the average fiber diameter D is 5 nm or more and 250 nm or less.
3. 3. The membrane electrode assembly for a fuel cell according to claim 1, wherein a ratio of an arithmetic mean roughness Ra1 of the first main surface to an arithmetic mean roughness Ra2 of the second main surface: Ra1 / Ra2 satisfies 2≦Ra1 / Ra2.
4. 4. The fuel cell membrane electrode assembly according to claim 1, wherein the catalyst layer has a thickness T of 1 μm or more and 20 μm or less.
5. 5. The membrane electrode assembly for a fuel cell according to claim 1, wherein the arithmetic mean roughness Ra1 of the first main surface is 30% or less of a thickness T of the catalyst layer.
6. 6. The membrane electrode assembly for a fuel cell according to claim 5, wherein the arithmetic mean roughness Ra1 of the first main surface is 10% or more of a thickness T of the catalyst layer.
7. 7. The membrane electrode assembly for a fuel cell according to claim 6, wherein the arithmetic mean roughness Ra2 of the second main surface is 5% or less of a thickness T of the catalyst layer.
8. 8. The fuel cell membrane electrode assembly according to claim 1, wherein the catalyst layer has a thickness T of 5 μm or more and 10 μm or less.
9. 9. The membrane electrode assembly for a fuel cell according to claim 8, wherein the first main surface has an arithmetic mean roughness Ra1 of 2 μm or less.
10. 10. The membrane electrode assembly for a fuel cell according to claim 9, wherein the first main surface has an arithmetic mean roughness Ra1 of 0.6 μm or more.
11. 11. The membrane electrode assembly for a fuel cell according to claim 10, wherein the second main surface has an arithmetic mean roughness Ra2 of 0.3 μm or less.
12. a gap is provided at an interface between the catalyst layer and the gas diffusion layer; a dimension Wk of the gap in a direction along the interface is equal to or less than a thickness T of the catalyst layer, 12. The fuel cell membrane electrode assembly according to claim 1, wherein a dimension Ws of the gap in a thickness direction of the catalyst layer is equal to or less than Wk.
13. An electrolyte membrane; A pair of catalyst layers disposed so as to sandwich the electrolyte membrane; a pair of gas diffusion layers arranged to sandwich the electrolyte membrane with the pair of catalyst layers interposed therebetween; The pair of catalyst layers each have a first main surface and a second main surface, The gas diffusion layer is disposed on the first main surface side, The electrolyte membrane is disposed on the second main surface side, At least one of the pair of gas diffusion layers includes a conductive material and a polymer resin, the conductive material includes a fibrous carbon material; an average fiber diameter D of the fibrous carbon material is 25% or less of a thickness T of the catalyst layer, In a cross section in the thickness direction of the catalyst layer, the arithmetic average roughness Ra1 of the first main surface and the arithmetic average roughness Ra2 of the second main surface are Ra1>Ra2 A membrane electrode assembly for a fuel cell that satisfies the above relationship.
14. 14. A fuel cell comprising: the membrane electrode assembly for a fuel cell according to claim 13; and a pair of separators arranged to sandwich the membrane electrode assembly for a fuel cell, with the pair of gas diffusion layers provided in the membrane electrode assembly for a fuel cell interposed therebetween.
Citation Information
Patent Citations
Method of manufacturing membrane electrode assembly, membrane electrode assembly, and solid high polymer fuel cell
JP2009259782A
Gas diffusion layer
JP2019153416A
Gas diffusion layer for fuel cell, manufacturing method therefor, membrane electrode assembly, and fuel cell
WO2010050219A1
